Legal analysis of the regulation of armed conflict in the Papua region from the perspective of Emergency Constitutional Law - Eko Wibowo (Goodwood Publishing, 2023)
Purpose: The conflict in Papua has been the focus of discussion by various parties in the last few decades. Such a complex problem requires cooperation and comprehensive consideration from various parties. In practice, there are times when the country is in an abnormal state and requires emergency legal provisions. Emergency Constitutional Law provides a strong legal framework when the country is in an abnormal state, this is done with the main aim of protecting citizens and maintaining state sovereignty. Research methodology: This study uses a normative judicial method. The author's approach is a legislative approach by means of an inventory of applicable positive law and by looking at books that are the views of several experts. Results: Emergency Constitutional Law provides a strong legal framework when the country, all or part of its territory, is in an abnormal state. The conflict that occurred in Papua has met the requirements to be declared a state of emergency, because of the armed, political, and diplomatic wings in the OPM that threaten the security of citizens and the sovereignty of the state. The choice of Emergency Constitutional Law can be a consideration for the government to overcome the armed wing of the OPM, then the government can continue to resolve the conflict in Papua with planned programs without disturbing security.